Ultrasound-Induced Mechanoluminescence and Optical Thermometry Toward Stimulus-Responsive Materials with Simultaneous Trigger Response and Read-Out Functions - Ding, Yicong; So, Byoungjin; Cao, Jiangkun; Wondraczek, Lothar (Advanced Science, 2022)
Ultrasound-induced mechanoluminescence (USML) of Erbium-doped CaZnOS is reported. Using the fluorescence intensity ratio of the 2H11/2, 4S3/2 → 4I15/2 transitions of Er3+ allows for simultaneous temperature mapping at an absolute sensitivity of 0.003 K−1 in the physiological regime. The combination of USML, local heating, and remote read-out enables a feedback and response loop for highly controlled stimulation. It is found that ML is a result of direct energy transfer from the host material to Er3+, giving room for adapted spectral characteristics through bandgap modulation. ML saturation at high acoustic power enables independent control of local light emission and ultrasonic heating. Such USML materials may have profound implications for optogenetics, photodynamic therapy and other areas requiring local illumination, heating, and thermometry simultaneously.
CRIS-Team Scopus Importer:2023-04-20
Keywords: heating; mechanoluminescence; thermometry; ultrasonic